2012
DOI: 10.1186/2041-2223-3-20
|View full text |Cite
|
Sign up to set email alerts
|

Genomic view on the peopling of India

Abstract: India is known for its vast human diversity, consisting of more than four and a half thousand anthropologically well-defined populations. Each population differs in terms of language, culture, physical features and, most importantly, genetic architecture. The size of populations varies from a few hundred to millions. Based on the social structure, Indians are classified into various caste, tribe and religious groups. These social classifications are very rigid and have remained undisturbed by emerging urbanisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…It seems likely that a major demographic expansion of modern humans took place within India, and although the period of this expansion remains uncertain, it appears to have taken place 60,000-85,000 years before present (ybp) (Kivisild et al 1999;. The traces of socio-cultural, linguistic physiographical boundaries and evolutionary forces leading to diversity are well documented in the recent studies (Kivisild et al 1999;Metspalu et al 2004;Reich et al 2009;Tamang and Thangaraj 2012;Moorjani et al 2013). It has been shown that, with the exception of Africa, India harbours more genetic diversity than other comparable global regions (Papiha 1996).…”
Section: Molecular Genetic Variationmentioning
confidence: 81%
See 3 more Smart Citations
“…It seems likely that a major demographic expansion of modern humans took place within India, and although the period of this expansion remains uncertain, it appears to have taken place 60,000-85,000 years before present (ybp) (Kivisild et al 1999;. The traces of socio-cultural, linguistic physiographical boundaries and evolutionary forces leading to diversity are well documented in the recent studies (Kivisild et al 1999;Metspalu et al 2004;Reich et al 2009;Tamang and Thangaraj 2012;Moorjani et al 2013). It has been shown that, with the exception of Africa, India harbours more genetic diversity than other comparable global regions (Papiha 1996).…”
Section: Molecular Genetic Variationmentioning
confidence: 81%
“…The early history of its populations is like a jigsaw puzzle with many missing pieces. However there is enough anthropological and archaeological evidence to show that from time immemorial peoples of many different ethnic stocks, cultures and languages have entered India and contributed to the present day gene pool of the subcontinent (Bhasin et al 1994;Papiha, 1996;Kivisild et al 1999;Bhasin and Walter 2001;Kashyap et al 2004;Metspalu et al 2004;Reich et al 2009;Tamang and Thangaraj 2012;Moorjani et al 2013). There are traces of human activity in India around 200,000 B.C.…”
Section: Genesis Of Genomic Diversity In Indiamentioning
confidence: 99%
See 2 more Smart Citations
“…Dating back to time immemorial, this system is characterized by its well stratified, endogamous and close-cultural values, which could strongly prohibit any exchange from outside. Genetically, this restriction significantly control the gene flow between the population subgroups, which creates specific genetic patterns, that could make the groups either susceptible or resistant to various diseases [2][3].…”
Section: Introductionmentioning
confidence: 99%